Practical nutrition and hydration for dementia-friendly mealtimes - Martin, Lee, MSc, RD (Jessica Kingsley Publishers, 2019)
This book offers guidance on ensuring that individuals with dementia can maintain a high standard of nutritional intake alongside increased independence at mealtimes. It explains how dementia impacts on mealtime abilities, with practical guidance on how to enhance these abilities and interventions for overcoming common issues.